Association of Respiratory Tract Infections causing Alterations in Lung Parenchyma and Pulmonary Vasculature with Body Electrolyte Imbalance - Sadia Zia, Yasir Ali Bhatti, Nabeela Habib, Zulfiqar Ali, Afsheen Akbar, Beenish Sohail (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The assessment of serum electrolytes at the time of initial presentation of the patient with respiratory tract infection possibly causing lung parenchyma and pulmonary vasculature damage and serial monitoring during the stay could be beneficial in order to determine when and how to take remedial action when necessary. Methodology: A non-probability sampling was done on 139 subjects with suspected respiratory tract infection. For confirmation, culture, MTB PCR, COVID-19 testing was done to diagnose the nature of infection. Serum electrolytes were tested on chemical analyses Alinity instrument. Results: Most common infections found were COVID-19 and bacterial (n=59) collectively in a co-morbid state. Mycobacterium tuberculosis and fungal infections were also found in (n=8) each. Electrolytes imbalance was markedly observed in high prevalence amongst Tuberculosis and COVID-19 patients but also showed significant association with other respiratory investigated infections. Conclusion: A robust association of electrolyte imbalance was found in all cases presented with upper or lower respiratory tract infections.